Mass Increase with Speed Explained as a Relativistic Doppler Effect - SANDU, Constantin; BRASOVEANU, Dan (JOURNAL OF ADVANCES IN PHYSICS, 2017)
In this paper the authors show that the mechanism of mass increase is simple and can be explained by the wave feature of body micro-comps. From this point of view, the mass increase with speed perceived by a fixed observer is a Doppler relativistic effect.